The effect of temperature on the adsorption of 4-Nitrophenol onto palm shell based activated carbon - Norzilah, Abdul Halif, Dr. (Faculty of Computer Science and Information Technology, University of Malaya, 2014)
Link to publisher's homepage at http://ejum.fsktm.um.edu.my/